2005
DOI: 10.1016/j.orggeochem.2004.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic triterpene methyl ethers in recent lacustrine sediments (Lagoa do Caçó, Brazil)

Abstract: The lipid extracts of sediments collected from the Quaternary filling of a tropical lacustrine series (Lagoa do Caçó, Brazil) were investigated by gas chromatography-mass spectrometry (GC-MS). Various pentacyclic triterpene 3-methyl ethers (PTMEs) were present in the neutral fraction. Comparison of retention times and mass spectra with available standards allowed us to certify the presence of olean-12-en-3β-ol ME (β-amyrin ME), olean-18-en-3β-ol ME (miliacin), taraxer-14-en-3β-ol ME (crusgallin), fern-9(11)-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 46 publications
3
84
0
1
Order By: Relevance
“…The almost exclusive contribution of higher plant material to the sediment and contrasting conditions of degradation offer an outstanding context to monitor the diagenetic fate of higher plant triterpenes and other biomolecules. In previous reports on the biomarker content of these sediments, we discussed on the presence and the significance of onocerane I and of a series of pentacyclic triterpene methyl ethers 3 (Jacob et al, 2004b;Jacob et al, 2005). The numerous types of molecular skeletons that have so far been detected in these sediments (namely oleanane, ursane, taraxerane, bauerane, fernane, arborane and onocerane) strengthen the interest of biomarker studies to apprehend the different degradation pathways followed by triterpenes depending on (paleo)environmental conditions.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The almost exclusive contribution of higher plant material to the sediment and contrasting conditions of degradation offer an outstanding context to monitor the diagenetic fate of higher plant triterpenes and other biomolecules. In previous reports on the biomarker content of these sediments, we discussed on the presence and the significance of onocerane I and of a series of pentacyclic triterpene methyl ethers 3 (Jacob et al, 2004b;Jacob et al, 2005). The numerous types of molecular skeletons that have so far been detected in these sediments (namely oleanane, ursane, taraxerane, bauerane, fernane, arborane and onocerane) strengthen the interest of biomarker studies to apprehend the different degradation pathways followed by triterpenes depending on (paleo)environmental conditions.…”
Section: Introductionmentioning
confidence: 85%
“…The method for lipid extraction and separation was described elsewhere (Jacob et al, 2005). Briefly: one gram of dried sediment was ultrasonically extracted with acetonepentane (50:50 v/v).…”
Section: Extraction and Separation Of Free Lipidsmentioning
confidence: 99%
“…2 g) of each was extracted by way of automatic solvent extraction with a Dionex® ASE 200 using a mixture of CH 2 Cl 2 :MeOH (1:1). After removal of the solvent under N 2 , the extract was separated into neutral, acidic and polar fractions on aminopropyl-bonded silica as described by Jacob et al (2005). The neutral fraction was further separated into aliphatics, aromatics, ethers and esters, ketones and acetates, and alcohols by way of flash chromatography with a Pasteur pipette filled with activated silica (24 h at 120 °C, then deactivated with 5% H 2 O) and using a sequence of solvents of increasing polarity.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the presence of various Asteraceae seeds in a Late Bronze Age (905-869 BC) settlement on the shore of Lake le Bourget was related to their ethnobotanical properties, their consumption as human food or livestock fodder, dye and/or medicine (Bouby and Billaud, 2001;. Triterpenyl acetates thus extend the panel of biomarkers for past flora that can attest, in favourable cases, to human activities such as miliacin for millet (Jacob et al, 2008), other pentacyclic triterpene methyl ethers for Gramineae (Ohmoto et al, 1970;Jacob et al, 2005;Zocatelli et al, 2010), iso-and anteiso-monomethyl alkanes for culinary and aromatic herbs from the Lamiaceae family (Huang et al, 2011) and more generally those reported by Evershed (2008) with respect to archaeology. As with these other biomarkers, triterpenyl acetates can constitute reliable tools for tracing the presence of plants of economic interest.…”
Section: Potential Palaeoenvironmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation